2018
DOI: 10.1038/s41598-018-34511-7
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Lineage Potency and Plasticity of Stem Cells using Epigenetic Molecules

Abstract: Stem cells are considered as a multipotent regenerative source for diseased and dysfunctional tissues. Despite the promise of stem cells, the inherent capacity of stem cells to convert to tissue-specific lineages can present a major challenge to the use of stem cells for regenerative medicine. We hypothesized that epigenetic regulating molecules can modulate the stem cell’s developmental program, and thus potentially overcome the limited lineage differentiation that human stem cells exhibit based on the source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 71 publications
(78 reference statements)
1
3
0
Order By: Relevance
“…Our present results are in agreement with those by Dhaliwal and colleagues 24 , who demonstrated that epigenetic modifications like H3K9me3, H3K27me3 and H3K4me3 can be modulated to direct optimal osteoblastic differentiation within 72 hours, in the presence of osteogenic cues, and can regulate osteogenic differentiation of mesenchymal stem cells. An additional modification that we observed was trimethylation of H3K36 (Fig.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our present results are in agreement with those by Dhaliwal and colleagues 24 , who demonstrated that epigenetic modifications like H3K9me3, H3K27me3 and H3K4me3 can be modulated to direct optimal osteoblastic differentiation within 72 hours, in the presence of osteogenic cues, and can regulate osteogenic differentiation of mesenchymal stem cells. An additional modification that we observed was trimethylation of H3K36 (Fig.…”
Section: Discussionsupporting
confidence: 94%
“…It should be recalled that epigenetic regulation is deeply involved in bone homeostasis, and indeed histone modifications are considered the switches used by cells to control differentiation 20–24 . The expression of genes involved in bone remodeling, such as Runx2 and osteocalcin, is accompanied by the increase in methylation and acetylation of Runx2 promoter histones.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the stromal cells of GCTB express (pre)osteoblast markers, such as RUNX2, SATB2 and OSTERIX [109]. So epigenetic regulation is closely related to bone homeostasis, whereas histone modifications are implied in the control of cell differentiation [110][111][112]. In general, when cells are differentiating and maturing, they may lose pluripotency characterised by epigenetic changes in order to shut off genes dealing with stemness [113].…”
Section: H33-g34w Histomorphology and Denosumabmentioning
confidence: 99%
“…Hence, stem cell fate is modulated epigenetically upon integration of signals from outside the cell. Recent findings indicated that this mechanism can be coerced into diverting stem cell commitment to desired differentiation pathways: biochemical pre-treatment of MSCs with either of the five identified epigenetic modulators (Gemcitabine, Decitabine, I-CBP112, Chidamide, and SIRT1/2 inhibitor IV) enhanced osteogenesis in vitro [33]. Out of these, Gemcitabine and Chidamide successfully rescued the loss in osteogenic differentiation potential in MSCs obtained from aged donors, hence providing indication of the potential use of these small molecules as pharmacological agents against bone demineralization.…”
Section: In Vitro Testing Of Organic Coatings For Tissue Engineeringmentioning
confidence: 99%